Genetic conflicts in human pregnancy - Haig, David (Henry Stewart Talks, 2007)
The association of maternal provisioning of a fetus and opportunity cost, The relationship between maternal investment in fetus to the benefit to the fetus and the cost to its siblings, The maternal-fetus unit: genes and their direct benefit to the fetus and indirect cost to its siblings, Syndromes associated with the imprinted cluster of genes of human chromosome 11p15.5: Beckwith- Wiedemann syndrome and Silver-Russell syndrome, 3 potential areas for conflict during pregnancy: whether to carry/miscarry the embryo, nutrient quality of maternal blood and the volume of blood reaching the placenta, Placental hormones and fetal attempts to manipulate maternal physiology for fetal benefit, Maternal carbohydrate metabolism: glucose and insulin levels in the maternal blood, and maternal insulin sensitivity, The maternal-fetus blood circulation during pregnancy and the systemic blood supply shared between them
Reviewed at 2020/08/16